Kierunki wykorzystania i opłacalność produkcji truskawek - Gołębiewska, Barbara; Sobczak, Natalia (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2012)
The study provides an assessment of profitability of strawberries, grown for direct consumption in the traditional time of harvest. The aim was to determine the economic impact of strawberries in Poland and in the world, determine the direction of the use of strawberries in Poland and to determine the profitability of production and the factors shaping it. Our study was carried out for the period 2006–2011 in deliberately chosen farm, where for more than 10 years are produced strawberries. It was found that the fundamental determinants of profitability was the level of yields, the price obtained and the level of direct costs incurred in the production process.